Biomarker Preeklampsia Pada Ibu Hamil: Literature Review - Antu, Yuniarty; Iman, Dian Pratiwi (Madu Jurnal Ilmu Kebidanan, 2025)
Preeclampsia is a serious pregnancy complication that can cause maternal and neonatal morbidity and mortality if not properly managed. The high maternal mortality rate (MMR) and infant mortality rate (IMR) highlight the importance of early detection through predictive biomarkers that can serve as both preventive and monitoring tools. This study aims to evaluate various recent biomarkers that have the potential to serve as alternative supports for the diagnosis and monitoring of preeclampsia. The method used was a literature review with the application of inclusion and exclusion criteria to obtain relevant articles. The review identified ten articles that met the criteria, reporting several biomarkers that are relatively easy to perform, including hematological parameters (platelets, PLR ratio, hematocrit), serum lactate dehydrogenase (LDH), urea, creatinine, 25-hydroxyvitamin D, soluble Suppression of Tumorigenicity 2 (sST2), and Placental Growth Factor (PlGF). These biomarkers have shown diagnostic potential, although most still require further research to confirm their validity and sensitivity. The conclusion of this study is that hematological, biochemical, and placental growth factors may serve as alternative supportive examinations to facilitate early detection and monitoring of preeclampsia in the future.